Variations associated with the topography of mental foramen in black South African population from both human dry bone and Cone Beam Computed Tomography (CBCT) in mandibular samples - Stemmer, Ivonne Osekeng (My University, 2022)
The mental foramen is a crucial morphological landmark for multiple clinical or dental techniques. As such, knowing of the topography of the MF will aid clinicians in their clinical dental practice. Hence, the study aimed at determining the frequency of shape, position, number, and size of mental foramen (MF) among black South African population using dry mandibular bones and Cone Beam Computed Tomography (CBCT) scans of the mandible. Furthermore, the study determines influence of age and sex on the topography of mental foramen. The study was conducted on a total of 117 adult dry mandibles from Raymond A. Dart Collection of Human Skeletons based in the School of Anatomical Sciences, Faculty of Health Sciences, University of the Witwatersrand and 98 cone beam computed tomography (CBCT) scans of patients from Maxillo Facial and Oral Radiology Department at Wits Oral Health Centre, Charlotte Maxeke Academic Johannesburg Hospital, South Africa. The age range of the study sample and CBCT scan was 18-70 years. The shape, position and number of MF were observed. The metric dimension of MF was measured using a dental digital calliper on dry mandibular bones samples while and radiographic software for CBCT scans. The predominant location of MF was below the apex of second premolar. The shape of MF was mainly round and mostly bilateral. The vertical dimension of MF ranged between 2.48mm to 2.9mm, while the horizontal dimension was between 2.78mm to 3. 45mm.There were no significant and sex and age variations the topography. In conclusion, MF is located apex mandibular first premolar teeth. Also, no age and sex variation were noted in the topography and location of MF.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Dentistry to the Faculty of Health Sciences, School of Oral Health Sciences, University of Witwatersrand, Johannesburg, 2022